Accuracy evaluation of robot-guided laser osteotomy for dental implant bed preparation - a digital high-tech procedure - Thieringer, Florian M.; Walher, Regina; Halbeisen, Florian S.; Garnier, Quentin; Dragu, Adrian; Msallem, Bilal (Frontiers in Robotics and AI, 2025)
BackgroundThe accuracy and reproducibility of emerging high-tech procedures for dental implant placement need continuous evaluation. This is essential to facilitate the transition from conventional surgical guides to digital planning systems. This study investigates the accuracy of implant placement using robot-guided laser technology based on cone-beam computed tomography and intraoral scanning.MethodsTwelve dental implants were placed using surgical planning software and a robot-guided laser osteotome. The procedure incorporated surface scanning and enabled implant bed preparation using a robot-guided laser.ResultsThe mean overall 3D offset (mean ± SD) was 2.50 ± 1.30 mm at the base and 2.80 ± 1.00 mm at the tip, with a mean angular deviation of 6.60 ± 3.10°.ConclusionThe results demonstrate a considerably greater deviation than conventional guided systems. In the context of the high demands of oral surgery, accuracy is particularly susceptible to fluctuations, some of which may stem from intermediate workflow steps, particularly due to the early development stage of the robotic system. Notably, the absence of real-time depth measurement and robot-assisted implant placement remains a significant constraint. However, future technological advances are expected to address these challenges.